2014
DOI: 10.1371/journal.pone.0103156
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Cryptococcal Antigen Lateral Flow Assay Using Saliva in Ugandans with CD4 <100

Abstract: BackgroundCryptococcal meningitis can best be diagnosed by cerebrospinal fluid India ink microscopy, cryptococcal antigen detection, or culture. These require invasive lumbar punctures. The utility of cryptococcal antigen detection in saliva is unknown. We evaluated the diagnostic performance of the point-of-care cryptococcal antigen lateral flow assay (CrAg LFA) in saliva.MethodsWe screened HIV-infected, antiretroviral therapy naïve persons with symptomatic meningitis (n = 130) and asymptomatic persons with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In terms of the direct detection of pathogens, we created a POC meningitis menu that was systematically aimed at testing for enterovirus (NAAT), Streptococcus pneumoniae (NAAT), Neisseria meningitidis (NAAT), and herpesviruses, including herpes simplex and varicella-zoster viruses (NAAT), in cerebrospinal fluid collected from symptomatic patients clinically suspected of having meningitis (66). As for HIV-infected patients, an LFA detecting Cryptococcus neoformans polysaccharide capsule glucuronoxylomannan antigen performed adequately on CSF (67), plasma, serum, and urine samples (68), but tests on saliva were disappointing and should not be recommended (69). A few commercially available multiplexed NAATs currently under development would detect six bacteria, eight viruses, and two Cryptococcus species within 1 h.…”
Section: Meningitismentioning
confidence: 99%
“…In terms of the direct detection of pathogens, we created a POC meningitis menu that was systematically aimed at testing for enterovirus (NAAT), Streptococcus pneumoniae (NAAT), Neisseria meningitidis (NAAT), and herpesviruses, including herpes simplex and varicella-zoster viruses (NAAT), in cerebrospinal fluid collected from symptomatic patients clinically suspected of having meningitis (66). As for HIV-infected patients, an LFA detecting Cryptococcus neoformans polysaccharide capsule glucuronoxylomannan antigen performed adequately on CSF (67), plasma, serum, and urine samples (68), but tests on saliva were disappointing and should not be recommended (69). A few commercially available multiplexed NAATs currently under development would detect six bacteria, eight viruses, and two Cryptococcus species within 1 h.…”
Section: Meningitismentioning
confidence: 99%
“…Attempts to improve the specificity of the urine assay by altering the diluent have been unsuccessful, leading to a reduction in test sensitivity compared to serum LFA as reference and continued sub-optimal specificity (sensitivity decreasing from 100 % to 80 % and specificity increasing from 73.8 % to 91.5 %) [ 46 ]. Using samples of saliva, a recent Ugandan study found excellent specificity but poor sensitivity (88 % in symptomatic patients and only 27 % in asymptomatic patients) of the LFA in detecting cryptococcal antigenemia using serum/plasma samples for reference [ 73 ]. In a review of the published literature addressing performance of the LFA assay, median CSF sensitivity was 100 %, and median specificity was 97.7 %.…”
Section: The Changing Landscape Of Cryptococcal Diagnosticsmentioning
confidence: 99%
“…In a recent study in Uganda, there was perfect agreement between fingerstick whole blood, serum, and plasma CrAg LFA suggesting that testing from fingerstick whole blood is a viable option for detecting antigen CrAg, particularly in settings where phlebotomy is not available, or in patients with difficult venous access (15). The CrAg LFA has also been evaluated in both urine and saliva, but agreement with serum LFA was not sufficient to recommend routing screening using these fluids (16, 17). …”
Section: Introductionmentioning
confidence: 99%